LOYALITAS NASABAH DARI KEMUDAHAN PENGGUNAAN MOBILE BANKING - Evi Susanti; Novita Oktavianti Parera (STIE-JIC, 2021)
The research purpose is to examine customer loyalty from the variable of mobile banking usability mediated by customer satisfaction. Data were collected in a survey of M-Banking customers conducted from February to August 2020 via a questionnaire involving 105 respondents. The results showed that the ease of using M-Banking lead to customer satisfaction and also lead to bank loyalty, respectively. Considering the change in customer consumption patterns to using technology-based services, banks as service providers need to deliver service in easily, safely, and fast ways, such as internet banking and M-Banking. The research originality examines the direct effect of usability on customer loyalty, especially in conventional banks in Jakarta Province.